2020
DOI: 10.1016/j.conbuildmat.2020.118966
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of superabsorbent polymers and nanosilica for reduction of restrained shrinkage and strength compensation in cementitious mortars

Abstract: The water released by the SAPs is monitored by acoustic emission for the first time. The inclusion of SAPs mitigates the autogenous shrinkage of mortars. Nanosilica counteracts the loss of mechanical properties caused by the SAPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 48 publications
1
28
0
1
Order By: Relevance
“…The density of this solution is equal to 1.3 g/cm 3 , whereas the nanosilica particles have a nominal diameter of 12 nm and a specific surface area between 198 and 258 m 2 /g. In the mixtures containing nanosilica, the silica replaces cement in an amount of 2% dry powder by mass of the binder, which is the amount needed for optimal strength increase [25]. Furthermore, an additional amount of superplasticizer is added to the mixtures with HS-40 to obtain the same flow compared to the reference mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density of this solution is equal to 1.3 g/cm 3 , whereas the nanosilica particles have a nominal diameter of 12 nm and a specific surface area between 198 and 258 m 2 /g. In the mixtures containing nanosilica, the silica replaces cement in an amount of 2% dry powder by mass of the binder, which is the amount needed for optimal strength increase [25]. Furthermore, an additional amount of superplasticizer is added to the mixtures with HS-40 to obtain the same flow compared to the reference mixture.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, SAPs, nanosilica and a combination of both materials are added to a mortar reference mixture in order to obtain identical mechanical properties compared to the reference and to promote the self-healing capacity of the mix. Preceding research showed that, using a specific amount and type of both superabsorbent polymer and nanoreinforcement, it was possible to decrease the risk of autogenous shrinkage cracking, while maintaining the compressive strength of the reference material [25]. As this mix design was reported to be effective for the reduction of autogenous shrinkage, the question arises as to whether the mixture also possesses the ability of healing its own cracks.…”
Section: Introductionmentioning
confidence: 99%
“…This smoothens the effect of evaporation rate, ideally avoids the drop in internal relative humidity, and allows for continued hydration, enabling the cementitious material to resist the tensile forces leading to cracking. Practically, SAPs eliminate cracking as was revealed from the dedicated restrained ring tests in the time frame of the study (1 month) [8]. The contribution of the SAPs in controlling the shrinkage cracking is undeniable.…”
Section: Introductionmentioning
confidence: 90%
“…NS has shown the ability to increase the strength of a cementitious material due to its large surface area, which provides nucleation sites for the hydration of cement, early pozzolanic reaction and filler action. Recent results show that actually NS particles help to restore the mechanical properties in mixes with SAPs to the level of the reference material, while at the same time, the mixes benefit by the cracking mitigation action of SAPs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of SAPs and nanosilica in cementitious mixtures was investigated in previous studies and demonstrated the mitigation of autogenous shrinkage [ 23 ] and the improvement of the self-healing ability [ 24 ], while maintaining the compressive strength of the reference material. More specifically, the addition of 0.2% of SAPs reduced the compressive strength of mortars from 77.8 ± 2.4 MPa to 70.8 ± 3.6 MPa after 90 days of curing, while the substitution of cement by nanosilica resulted in a compressive strength of 93.2 ± 2.9 MPa.…”
Section: Introductionmentioning
confidence: 99%